2016
DOI: 10.1093/ckj/sfw089
|View full text |Cite
|
Sign up to set email alerts
|

Cuff extrusion in peritoneal dialysis: single-centre experience with the cuff-shaving procedure in five patients over a 4-year period

Abstract: Catheter-related infections in peritoneal dialysis (PD) remain a significant complication, and some patients with recurrent exit-site (ESI) and/or tunnel infections may experience external cuff extrusion. In these cases, cuff-shaving has been described as a possible course of treatment. During a 4-year period, there were 44 patients with PD at our department; all received double-cuffed Tenckhoff catheters. Six (13%) never started on PD. Five (13%) of the 38 active PD patients experienced cuff extrusion. Causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
0
19
0
4
Order By: Relevance
“…Depending on the magnitude of these shape memory forces and the proximity of the cuff to the exit site, straightening of the tubing may cause the cuff to extrude through the exit site. If the extruding cuff is not managed, it soon becomes seeded with bacteria and predisposes the patient to exit-site infection (141). A cuff that has completely extruded still remains a reservoir of bacteria in the vicinity of the exit site.…”
Section: Superficial Cuff Extrusionmentioning
confidence: 99%
“…Depending on the magnitude of these shape memory forces and the proximity of the cuff to the exit site, straightening of the tubing may cause the cuff to extrude through the exit site. If the extruding cuff is not managed, it soon becomes seeded with bacteria and predisposes the patient to exit-site infection (141). A cuff that has completely extruded still remains a reservoir of bacteria in the vicinity of the exit site.…”
Section: Superficial Cuff Extrusionmentioning
confidence: 99%
“…Debowski et al (7) reported 5 cases of cuff-shaving in patients who had developed cuff-extrusion. Although the reason for the procedure was extrusion of the external cuff, it had developed secondary to repeated ESIs in 4 patients and the cuff was likely to be infected, as none of the 5 patients experienced new ESIs after cuff-shaving had been performed.…”
Section: Discussionmentioning
confidence: 99%
“…For refractory ESIs, current guidelines suggest the timely replacement of the entire catheter, as this can prevent the inward dissemination of the infection, with the added advantage of permitting simultaneous replacement, thus avoiding prolonged periods on hemodialysis (47). Alternatively, the replacement of the infected external tubing segment by catheter splicing (811), or unroofing of the tunnel tract and shaving/removal of the superficial catheter cuff (12 13 14 15 16 17 18-19) have been proposed. On the contrary, our method is based on the assumption that the removal of the superficial cuff rather than the entire catheter is adequate to eradicate the infection since it is known to be an ongoing reservoir of infection.…”
Section: Discussionmentioning
confidence: 99%